Negotiating the sweet spot: personal negotiations - Thompson, Leigh (Henry Stewart Talks, 2021)
What is the Sweet Spot, Relationship negotiations, Preconceptions about negotiating -Negotiation hacks, Perspective-taking, Suspicion, Disappointment, Shoulder-to-shoulder, Silence, Problem solving